Integrating sustainable development into the curriculum - Sengupta, Enakshi; Blessinger, Patrick; Yamin, Taisir Subhi (Innovations in higher education teaching and learning ;, 2020)
Creating a sustainable future is one of the biggest challenges that we face as a human race. This is often made even harder by the apathy of many towards the need for sustainability. Education will play a crucial role in finding a solution to the global climate crisis, by shaping future generations who are informed, enlightened and ready to take action. This book explores the value of institutions of higher education in leading the way on the topic of sustainability education by ensuring that it is well entrenched in the curriculum, as well as in everyday practice and lifestyles. This unique volume features authors from different parts of the world who narrate their own experience of integrating sustainability into their curriculum, and teaching sustainability to students. By exploring the idea that education and sustainability should be seen as intrinsically linked if we are to see global change, this important text will prove invaluable for leaders, scholars and policy specialists in higher education.